Peningkatan Moderasi Beragama dalam Masyarakat di MAS Al Hikmah Bandar Lampung - Munawaroh; Nando Apriyansyah (ISLAM EDU : Jurnal Ilmiah Pendidikan Agama Islam, 2023)
This article discusses religious moderation by the community in Mas Al Hikmah, with a case study of madrasas with the aim of uncovering the role and learning of religious moderation. The research methodology is descriptive case study at the Al Hikmah Bandar Lampung Private Aliyah Madrasah with observation, interview and documentation as a data collection tool. The results of this study prove that religious moderation learning conducted in the Al Hikmah Lampung Private Aliyah Madrasah is centralized in 4 groups, namely education in class, dormitory, outchamp and rihlah iqtishodiyah which is elaborated in 6 activities such as group discussions, cross learning, visits to places of worship , Assignment of reflection, social service activities, cultural exchange and can be collected that religious moderation activities carried out inside and outside the classroom can help students in understanding and respecting religious differences by inclusive, attentive and interrelationship